2022
DOI: 10.1590/s1980-657420220017121
|View full text |Cite
|
Sign up to set email alerts
|

TGfU in the teaching of handball at school: impacts on the motor coordination and technique in the game

Abstract: This study investigated the impact of a handball-teaching program through the understanding of the TGfU on motor coordination (MC) and technical skills of students. Methods: The sample consisted of 43 students of both genders, with a mean age of 14.3 years (± 0.46), divided into two groups, G1 -Teaching Games of Understanding (TGfU) and G2 -TGfU + MC, and both received 20 classes. We used the Körperkoordinationstest für Kinder (KTK) for the assessment of MC and the Game Performance Assessment Instrument (GPAI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Such expectations reinforce that skills must be taught so that players can understand and deal with different game situations, use spaces properly, offering options to their partners, as the players with the ball are required to make the best possible decisions (Gréhaigne & Godbout 1995, Morales-Belando et al 2018, Seco 2005. In this sense, some studies have shown the importance of teaching through games and situations that involve complexity for decisionmaking in handball in different contexts (Dorak et al 2018, Mazzardo et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Such expectations reinforce that skills must be taught so that players can understand and deal with different game situations, use spaces properly, offering options to their partners, as the players with the ball are required to make the best possible decisions (Gréhaigne & Godbout 1995, Morales-Belando et al 2018, Seco 2005. In this sense, some studies have shown the importance of teaching through games and situations that involve complexity for decisionmaking in handball in different contexts (Dorak et al 2018, Mazzardo et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Inside health, interventions aimed at preventing injuries to adolescent athletes through strength training have proven effective in protecting the athlete's health and physical integrity 41,42 . Several other studies have chosen to apply a school intervention with handball under different contexts aimed directly at performance within the context of specific training [43][44][45] .…”
Section: Discussionmentioning
confidence: 99%
“…In the last 5 years, various methodologies have been applied in different school contexts to teach handball, such as teaching games for understanding, integrative methodology, and the Handball at School program, with very positive results [ 11 , 12 , 13 ]. Non-linear pedagogy (NLP) has also been used as an alternative to develop motor skills through mini handball [ 14 ], as, according to this methodology, the human being is considered a biological system with constant interaction between all its component elements (physical, biochemical, emotional, etc.…”
Section: Introductionmentioning
confidence: 99%